2019
DOI: 10.1055/s-0039-1683921
|View full text |Cite
|
Sign up to set email alerts
|

The “Diagonal” Lesion: A New Type of Combined Injury Pattern Involving the Impingement Fracture of Anteromedial Tibial Plateau and the Injury of Posterior Cruciate Ligament and Posterolateral Corner

Abstract: The purpose of this study was to investigate the incidence and clinical characteristics of the “diagonal” lesion. A total of 273 consecutive patients with combined posterolateral corner (PLC) and posterior cruciate ligament (PCL) injuries were retrospectively analyzed. All preoperative knee joint evaluations were reviewed including the computed tomography, the anteroposterior (AP) view, the lateral view, the full-length long-standing AP view, and the physical examination results with the patient under anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…Up to now, the injury mechanism of this combined injury has been described as follows: under the action of forces of hyperextension and varus rotation, the medial femoral condyle and the anteromedial tibial plateau collide with each other, resulting in the fracture of the latter [ 7 , 8 , 14 16 ]. Simultaneously, the PLC is injured and the posterolateral joint space is widened.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Up to now, the injury mechanism of this combined injury has been described as follows: under the action of forces of hyperextension and varus rotation, the medial femoral condyle and the anteromedial tibial plateau collide with each other, resulting in the fracture of the latter [ 7 , 8 , 14 16 ]. Simultaneously, the PLC is injured and the posterolateral joint space is widened.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, it has been reported that the rate of clinical missed diagnosis of the “diagonal” lesion can reach 78.6% (11 /14). Such an error can ultimately lead to knee instability and severe varus deformity of the lower extremity [ 8 ]. Consequently, for this combined injury, it is important to avoid missed diagnosis or misdiagnosis in the initial examinations of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations